2018
DOI: 10.1038/s12276-018-0175-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective blockade of spinal D2DR by levo-corydalmine attenuates morphine tolerance via suppressing PI3K/Akt-MAPK signaling in a MOR-dependent manner

Abstract: Morphine tolerance remains a challenge in the management of chronic pain in the clinic. As shown in our previous study, the dopamine D2 receptor (D2DR) expressed in spinal cord neurons might be involved in morphine tolerance, but the underlying mechanisms remain to be elucidated. In the present study, selective spinal D2DR blockade attenuated morphine tolerance in mice by inhibiting phosphatidylinositol 3 kinase (PI3K)/serine–threonine kinase (Akt)-mitogen activated protein kinase (MAPK) signaling in a μ opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…Although mechanisms underlying morphine-mediated processes remain the subject of much debate, morphine stimulation activates G protein-coupled opioid receptors and then induces significant molecular changes inside the cell, such as an inhibition of adenylate cyclase activity, and activation of potassium channels (Qu et al, 2017;Yang et al, 2019). In addition, other signalling pathways, including mitogenactivated kinases (MAPK), b-arrestin, phospholipase C, protein kinase, PI3K, and extracellular signal-regulated kinase (ERK) pathways, are also involved in morphine activity (Bianchi et al, 2010;Zhang and Pan, 2010;Dai et al, 2018;Shen et al, 2018;de Freitas et al, 2019;Dekan et al, 2019;Listos et al, 2019). Recently, the role of oxidative stress in morphine action has been paid more attention.…”
Section: Morphine Addictionmentioning
confidence: 99%
“…Although mechanisms underlying morphine-mediated processes remain the subject of much debate, morphine stimulation activates G protein-coupled opioid receptors and then induces significant molecular changes inside the cell, such as an inhibition of adenylate cyclase activity, and activation of potassium channels (Qu et al, 2017;Yang et al, 2019). In addition, other signalling pathways, including mitogenactivated kinases (MAPK), b-arrestin, phospholipase C, protein kinase, PI3K, and extracellular signal-regulated kinase (ERK) pathways, are also involved in morphine activity (Bianchi et al, 2010;Zhang and Pan, 2010;Dai et al, 2018;Shen et al, 2018;de Freitas et al, 2019;Dekan et al, 2019;Listos et al, 2019). Recently, the role of oxidative stress in morphine action has been paid more attention.…”
Section: Morphine Addictionmentioning
confidence: 99%
“…In our previous study, levo -corydalmine ( l -CDL) was found to significantly attenuate neuropathic pain in CCI rats 31 , 32 . Moreover, our previous research showed that l -CDL exhibits micromolar affinity for both D1DR and D2DR with half maximal inhibitory concentrations (IC50) of 0.20 μM and 0.86 μM, respectively 33 . D1DR, D2DR, and D1–D2DR heterodimer agonists were used to investigate whether the l -CDL-induced analgesic effect is mediated by the D1–D2DR complex in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study by Dai et al [21], it was demonstrated that l -CDL could attenuate morphine tolerance in rats with chronic bone cancer pain. This compound proved to be an antagonist of D 2 R as it inhibited dopamine-induced calcium release in CHO-K1 cells expressing D 2 R. A similar effect, as observed in their previous study [35], was noticed upon coadministration of l -CDL with morphine, and the effect was reversed upon addition of quinpirole, a D 2 R agonist in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies clearly suggest an interplay between D 2 R and MOR, the link between D 2 R and opioid analgesia, as well as tolerance, still remains unclear as there are reports for both D 2 R antagonists and D 2 R agonists to attenuate morphine tolerance [21,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation